2004
DOI: 10.1002/cjg2.3545
|View full text |Cite
|
Sign up to set email alerts
|

Regionalization of the Recent Tectonic Stress Field in China and Adjacent Regions

Abstract: According to the stress state and force source character, the recent tectonic stress field of China and adjacent regions is classified into four classes: The first order tectonic stress district is mostly controlled by the geometry of plate boundary and the force acting on plate boundary, the stress action of this stress field shows uniformity and stability in large areas and long time. The stress action of second order tectonic stress district shows correlation in a large area. This stress field is controlled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 6 publications
6
50
0
Order By: Relevance
“…4). In accordance with the principal regional stress direction (Xie et al, 2003;Chen et al, 2012b), the local fracture zones are mainly oriented in Northeast direction, and only 6 fracture zones longer than 5 km are noticed (Fig. 5).…”
Section: Fracture Zone Effectssupporting
confidence: 70%
“…4). In accordance with the principal regional stress direction (Xie et al, 2003;Chen et al, 2012b), the local fracture zones are mainly oriented in Northeast direction, and only 6 fracture zones longer than 5 km are noticed (Fig. 5).…”
Section: Fracture Zone Effectssupporting
confidence: 70%
“…Comparing with average P axis directions with those of previous work [14][15][16][17], we found that the maximal principle pressure directions in central Yunnan block and southwest Yunnan block are in good consistence. For this reason, the regional stress field calculated from average CMT P axis directions can well describe the background stress field in each of the subarea.…”
Section: Stress Field and Gps Strain Fieldsupporting
confidence: 62%
“…In recent years, accumulation of stress measurement, fault slip measurement and focal mechanism data, especially establishment of crustal stress database in China and its adjacent areas (Xie et al, 2003), lays a solid foundation for the study on determination of Chinese tectonic stress field. By using this database, Xie et al (2004) summarized the fundamental features of Chinese tectonic stress field and divided the Chinese mainland into different tectonic stress blocks. In this study, we will divide the whole China into 2°×2° subregions and determine the tectonic stress direction and stress ratio in each subregion by using this database and CMT catalogue from 1976 to 2005.…”
Section: Introductionmentioning
confidence: 99%